1988
DOI: 10.1677/joe.0.1190483
|View full text |Cite
|
Sign up to set email alerts
|

Precopulatory behaviour in the male hamster: effect of the 5α-reductase inhibitor 17β-N,N-diethylcarbamoyl-4-aza-5α-androstan-3-one

Abstract: Three independent components of hamster masculine behaviour (approaching, leaving and sniffing the female) have been shown to depend on both androgenic and oestrogenic action. The behavioural role of 5 alpha-reduced androgens was assessed by blocking 5 alpha-reduction of testosterone by means of 17 beta-N,N-diethylcarbamoyl-4-aza-5 alpha-androstan-3-one (4-MA) through slow-release silicone elastomer implants. Three dose levels of 4-MA were given to intact, sexually active males. The probability of approaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, DHT can reinstate masculine calling and amplectic clasping in amphibians (Kelley and Pfaff, 1976;Moore and Miller, 1983;Wetzel and Kelley, 1983;Penna et al, 1992) and copulatory postures in whiptail lizards (Lindzey and Crews, 1986;Mayo and Crews, 1987;Wade et al, 1993). In other species, treatment with 5␣-reductase inhibitors attenuates T-mediated behaviors, such as chemoinvestigation in male hamsters (Steel and Hutchison, 1988) and penile erections in rats (Bradshaw et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…For example, DHT can reinstate masculine calling and amplectic clasping in amphibians (Kelley and Pfaff, 1976;Moore and Miller, 1983;Wetzel and Kelley, 1983;Penna et al, 1992) and copulatory postures in whiptail lizards (Lindzey and Crews, 1986;Mayo and Crews, 1987;Wade et al, 1993). In other species, treatment with 5␣-reductase inhibitors attenuates T-mediated behaviors, such as chemoinvestigation in male hamsters (Steel and Hutchison, 1988) and penile erections in rats (Bradshaw et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a histological analysis using Col-GFP mice revealed that type 1 collagen levels are decreased in the nasal mucosa of aged mice; thus, the quantity and quality of collagen-expressing mesenchymal cells might change with age. Despite clinical evidence that olfaction decreases with age, the mechanism underlying the upregulation of genes involved in olfactory transduction has yet to be definitively determined; however, it is speculated to be a compensatory response to olfactory impairment or an increase in the expression of genes in the nasal mucosa involved in olfactory transduction, such as Syt10 (Cao et al, 2011 ), Bpifb9b (Kuntová et al, 2018 ), and Srd5a2 (Steel and Hutchison, 1988 ).…”
Section: Discussionmentioning
confidence: 99%